Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Pada Rumah Sakit TK II Pelamonia Makassar - Bayu Pamungkas; Chalid Imran Musa; Zainal Ruma; Romansyah Sahabuddin; Burhanuddin (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
This study aims to determine whether there is an effect of work discipline on employee performance at TK II Pelamonia Makassar Hospital. The type of data used in this study is quantitative data obtained from questionnaires distributed and related to the problem under study with a sample size of 67 people. Data were analyzed using a simple linear regression analysis method with the help of SPSS 23 data processing to prove the hypothesis. The results showed that the work discipline variable had a significant level of 0.000, which was less than 0.05. The coefficient value of 0.471 indicates a positive influence on the dependent variable. This means that Ha is accepted and Ho is rejected so that it can be said that work discipline has a positive and significant effect on employee performance